Slovene students’ writing skills in portuguese - Müller, Blažka (Vestnik za tuje jezike, 2024)
This paper seeks to identify and reflect on the difficulties Slovene students face when writing in European Portuguese, in order to present didactic strategies tailored to address such challenges. Acknowledging that writing is a complex and cognitively demanding task, our research stresses the importance of fostering learners’ written and linguistic competencies, abilities that are deeply intertwined. As such, the first part of our theoretical framework provides a description of general difficulties associated with writing in a second language. Subsequently, it contrasts linguistic domains in Portuguese and Slovene, while offering insights into common issues Slovene students encounter when writing in Portuguese. A qualitatively assessed pilot study, involving 1st- and 2nd-year university students, tasked with expository writing, confirmed that the issues identified in our review of the literature – concerning format, information, lexis and syntax – are areas that demand extra attention and time. In terms of grammar, more specifically, the analysis we carried out has proven that there are word classes and syntactic structures in Portuguese which pose challenges for Slovene students, due to their unfamiliar features. According to our results, problems with deter-miners, their contraction with prepositions, past verbal tenses and the placement of pronouns were particularly significant. Based on these domains, we suggest the use of didactic strategies which acknowledge writing as an iterative process, aimed at helping students overcome their difficulties, while developing self-regulatory, metalinguistic, and creative problem-solving skills. Our scientif-ic contribution lies in the promotion of pedagogical actions based on the efficient contrast between languages, the creative use of digital resources and materials presenting authentic discourse.
Keywords: didactics; didaktika; jezikovne spretnosti; linguistic skills; pisno izražanje; portugalščina; portugalščina kot drugi jezik; Portuguese as a Second Language; second language writing; Slovene university students; slovenski univerzitetni študentje; tuji jeziki